Activity of Human Apurinic/Apyrimidinic Endonuclease APE1 Toward Damaged DNA and Native RNA With Non-canonical Structures - Davletgildeeva, Anastasia T.; Kuznetsova, Alexandra A.; Fedorova, Olga S.; Kuznetsov, Nikita A. (Frontiers in Cell and Developmental Biology, 2020)
The primary role of apurinic/apyrimidinic (AP) endonuclease APE1 in human cells is the cleavage of the sugar-phosphate backbone 5′ to an AP-site in DNA to produce a single-strand break with a 5′-deoxyribose phosphate and 3′-hydroxyl end groups. APE1 can also recognise and incise some damaged or modified nucleotides as well as possesses some minor activities: 3′-5′ exonuclease, 3′-phosphodiesterase, 3′-phosphatase and RNase H. A molecular explanation for the discrimination of structurally different substrates by the single active site of the enzyme remains elusive. Here we report a mechanism of target nucleotide recognition by APE1 as revealed by the results of an analysis of the APE1 process involving damaged DNA and native RNA substrates with non-canonical structures. The mechanism responsible for substrate specificity proved to be directly related to the ability of a target nucleotide to get into the active site of APE1 in response to an enzyme-induced DNA distortion. It was found for the first time that APE1 can cleave even undamaged DNA within non-B-form structures thereby strongly supporting the identified mechanism of target nucleotide recognition.